Biopreservation strategies in combination with mild high pressure treatments in traditional Portuguese ready-to-eat meat sausage - Castro, S. M. (2017)
Thrombomodulin (TM) is an endothelial cell membrane protein that acts as a major cofactor in the protein C anticoagulant pathway. The EGF-like domains 4-6 of TM (TM456) are essential for PC activation. In this study, we proposed a liposomal recombinant TM conjugate to mimic the membrane TM structure and its anticoagulant activity. First, a DSPE-PEG2000-TM456 was successfully synthesized by site-specific conjugation of azido-TM456 with DSPE-PEG2000-DBCO via copper-free click chemistry quantitatively. Then, liposome-TM456 was fabricated via direct liposome formation with the DSPE-PEG2000-TM456 and other lipids. This liposomal formulation of TM456 retained protein C activation activity as that of TM456. Also, liposome-TM456 was much more stable and had a longer plasma half-life than TM456 and DSPE-PEG2000-TM456, respectively. Moreover, liposome-TM456 showed in vivo anticoagulant effect by decreasing the mortality from 80% to 20% in a thrombin-induced thromboembolism mouse model. The reported liposome-TM456 conjugate mimics the endothelial TM anticoagulation activity and may serve as an effective anticoagulant agent candidate for future development.